2020
DOI: 10.1101/2020.07.10.20150797
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic associations for two biological age measures point to distinct aging phenotypes

Abstract: Biological age measures outperform chronological age in predicting various aging outcomes, yet little is known regarding genetic predisposition. We performed genome-wide association scans of two age-adjusted biological age measures (PhenoAgeAcceleration and BioAgeAcceleration), estimated from clinical biochemistry markers1,2 in European-descent participants from UK Biobank. The strongest signals were found in the APOE gene, tagged by the two major protein-coding SNPs, PhenoAgeAccel-rs429358 (APOE e4 determinan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…Given that PhenoAge and PhenoAccelAge were estimated with assessments at admission, the impact of pre-admission PhenoAge values and how its associated change may be related to reduced physiological reserve, diminished intrinsic capacity or frailty remains to be further studied [31][32][33]. Lastly, we only used PhenoAge and PhenoAgeAccel to estimate adaptive responses potentially linked to aging; however, it is well known that different biological age estimations may illustrate distinct points of view of the aging process [34]. Prospective studies assessing aging measures before, during and after the infection are necessary to further elucidate the impact of premature aging on the clinical course of COVID-19 patients; additionally, other parameters should be taken into account, such as imaging features, immunophenotyping and histopathological findings.…”
Section: Discussionmentioning
confidence: 99%
“…Given that PhenoAge and PhenoAccelAge were estimated with assessments at admission, the impact of pre-admission PhenoAge values and how its associated change may be related to reduced physiological reserve, diminished intrinsic capacity or frailty remains to be further studied [31][32][33]. Lastly, we only used PhenoAge and PhenoAgeAccel to estimate adaptive responses potentially linked to aging; however, it is well known that different biological age estimations may illustrate distinct points of view of the aging process [34]. Prospective studies assessing aging measures before, during and after the infection are necessary to further elucidate the impact of premature aging on the clinical course of COVID-19 patients; additionally, other parameters should be taken into account, such as imaging features, immunophenotyping and histopathological findings.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 583 single‐nucleotide polymorphisms (SNPs) based on the up‐to‐date largest GWAS of the six sleep behaviors in ~1.3 million participants from 23andMe and UK Biobank cohorts were selected for the GRS of six sleep behaviors and sleep index (reported p ‐value < 5 × 10 −8 ) (Jansen et al, 2019). For the GRS of AAs, we used the latest and the only GWAS on both BAs (Kuo et al, 2021), which, respectively, reported 16 and 29 SNPs that were robustly associated with KDM‐biological age and PhenoAge (reported p ‐value <5 × 10 −8 ). Because the SNPs were evaluated in pruned genetic data in previous studies, no further loci pruning was conducted in our study.…”
Section: Methodsmentioning
confidence: 99%
“…The association with COVID-19 severity that these diseases share with PhenoAge may reflect the role of underlying immune-related pathways. In our recent genome-wide association study (GWAS) on accelerated PhenoAgeAccel, we observed enrichment for biological processes involved in immune system, cell function, and carbohydrate homeostasis [ 17 ]. A methylation clock (DNAmPhenoAge) trained using PhenoAge as a surrogate for biological age, instead of chronological age, has been shown to be associated with activation of pro-inflammatory, interferon, DNAm damage repair, transcriptional/translational signaling, and various markers of immunosenescence: a decline of naïve T cells and shortened leukocyte telomere length [ 2 ].…”
Section: Discussionmentioning
confidence: 99%